La Summer school “Emilio Sereni” sulla storia del paesaggio agrario italiano - Bonini, Gabriella (Scienze del Territorio, 2017)
The Summer School “History of the Italian agricultural landscape” is dedicated to Emilio Sereni and has been taking place for 9 years, always in the last week of August, at the Alcide Cervi Institute in Gattatico (RE). For the first five years, as in Emilio Sereni’s writing, the objects of study have been following the chronological order, from the prehistoric and ancient age to the XXI century. The highlighted concepts have been mainly those of heritage-territory and citizenship-territory. Later, the studies on landscape have been conducted through a comparative reading of several disciplines and has been seen as the result of a territoriality relationship, in an interactive long term process, between a society and a territory. The landscape as a product of the incessant human activity, the visible manifestation of the co-evolution process between local society and physical environment. This is the legacy that Emilio Sereni left to us in his definition: our agricultural landscape is “that form that humans, in the course and for the purpose of agricultural production, consciously and systematically gives to the natural landscape”. The Emilio Sereni Summer School is an experience that shows how, starting from the history of landscape, can widen the perspective to other disciplines as for territorial reading and planning. Rossano Pazzagli is the current Director.